The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1149/2162-8777/aceaa8
|View full text |Cite
|
Sign up to set email alerts
|

1 mm2, 3.6 kV, 4.8 A NiO/Ga2O3 Heterojunction Rectifiers

Abstract: Large area (1 mm2) vertical NiO/β n-Ga2O/n+ Ga2O3 heterojunction rectifiers are demonstrated with simultaneous high breakdown voltage and large conducting currents. The devices showed breakdown voltages (VB) of 3.6 kV for a drift layer doping of 8 x 1015 cm-3, with 4.8 A forward current. This performance is higher than the unipolar 1D limit for GaN, showing the promise of β-Ga2O3 for future generations of high-power rectification devices. The breakdown voltage was a strong function of drift region carrier conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…Additionally, they successfully demonstrated high-BV devices with a maximum of 6.5 kV, achieved through thermal annealing optimization [57]. They also showcased p-n diodes with a 3.6 kV BV and a 4.8 A current capability within a 1 mm 2 device area [61].…”
Section: P-nio X /β-Ga 2 O 3 Heterojunctionmentioning
confidence: 95%
“…Additionally, they successfully demonstrated high-BV devices with a maximum of 6.5 kV, achieved through thermal annealing optimization [57]. They also showcased p-n diodes with a 3.6 kV BV and a 4.8 A current capability within a 1 mm 2 device area [61].…”
Section: P-nio X /β-Ga 2 O 3 Heterojunctionmentioning
confidence: 95%
“…To contextualize the present study, Figure 6 presents a compilation of reported specific Ron versus V B outcomes documented in the literature for rectifiers in the Ampere-class range. This compilation encompasses conventional Schottky barrier or JBS rectifiers, as well as NiO/Ga 2 O 3 heterojunction rectifiers [22,25,[29][30][31]33,35]. The theoretical lines representing the one 1D unipolar limits of SiC, GaN, and Ga 2 O 3 are also included for reference.…”
Section: Referencementioning
confidence: 99%
“…A promising recent development entails the incorporation of NiO as a p-type conducting layer to engender p-n heterojunctions with the n-type Ga 2 O 3 [21,, partially mitigating the inherent absence of native p-type doping capabilities in Ga 2 O 3 . Nevertheless, formidable challenges persist, encompassing the optimization of edge termination and effective heat dissipation management, vital prerequisites for ensuring device reliability [1,5,20,25,[32][33][34][35][36][37][38]. Another paramount endeavor entails the realization of larger area devices capable of facilitating substantial conduction currents, while concurrently upholding their kV-level breakdown characteristics [1,22,25,[29][30][31]33,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimization of the heterojunction rectifier device structure is crucial to achieve both high V B and low R ON , as well as providing management of the maximum electric fields within the structure to enhance further the device voltage blocking capability [40][41][42][43][44][45]. The design variables include the thickness and doping of the layers, doping in the drift layer and the use of the NiO as a guard ring by extending it beyond the metal cathode [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. In this paper, we report an investigation of the uniformity of achieving high V B and low R ON in heterojunction rectifiers, the effect of drift layer doping and the temperature dependence of the performance of NiO/Ga 2 O 3 to 600 K.…”
Section: Introductionmentioning
confidence: 99%